2010
DOI: 10.2174/092986610790780350
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Defensin from Cowpea (Vigna unguiculata (L.) Walp.)

Abstract: Using Phaseoleae defensins available in databases, a putative defensin gene was isolated in cowpea (Vigna unguiculata (L.) Walp.) and cloned from genomic cowpea DNA. The putative mature defensin sequence displays the characteristic defensins residues arrangement, secondary and tertiary structures were predicted and splicing analysis was performed. Using RT-PCR, defensin expression and differences in response to biotic stimuli between infected and non infected plants were tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…They play an important role in the protection of germinating plant seeds, developing seedlings and reproductive structures of plants [42-44] and have been isolated from roots [44-46], vegetative tissues and reproductive structures such as flowers and fruits [45,47-55]. The majority of characterized plant defensins show a constitutive pattern of expression, with an induction in expression in response to pathogen attack, wounding and some abiotic stresses [20,44-46]. Recently it was shown that pathogen-induced expression of Arabidopsis plant defensins is dependent on ENHANCED DISEASE RESISTANCE1 (EDR1), which interferes with the repressor function of MYC2 allowing for defensin gene expression [56].…”
Section: Introductionmentioning
confidence: 99%
“…They play an important role in the protection of germinating plant seeds, developing seedlings and reproductive structures of plants [42-44] and have been isolated from roots [44-46], vegetative tissues and reproductive structures such as flowers and fruits [45,47-55]. The majority of characterized plant defensins show a constitutive pattern of expression, with an induction in expression in response to pathogen attack, wounding and some abiotic stresses [20,44-46]. Recently it was shown that pathogen-induced expression of Arabidopsis plant defensins is dependent on ENHANCED DISEASE RESISTANCE1 (EDR1), which interferes with the repressor function of MYC2 allowing for defensin gene expression [56].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial peptides (AMPs) are important components of the first line defense of innate immune systems in various species, including mammals, amphibians, insects and plants (Broekaert et al 1995;Thomma et al 2002;Castro and Fontes 2005;Senyürek et al 2009;Padovan et al 2010). AMPs show broad-spectrum antimicrobial activity against a wide range of pathogens (Zasloff 2002;Senyürek et al 2009), and their mode of action is not completely understood (Brodgen 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sequence, amino acid arrangement, splicing analysis, secondary and tertiary structures of mature putative defensin peptide showed similarity towards a typical defensin peptide. Response of biotic stimuli on pathogen treated and untreated plants were examined by the expression level of defensin gene, using RT-PCR 63 . A list of defensin peptides, their origin and action against specific microorganisms is listed in Table 2.…”
Section: Six Main Families Of Pampsmentioning
confidence: 99%